Rational Design and Evaluation of an Artificial Escherichia coli K1 Protein Vaccine Candidate Based on the Structure of OmpA - Gu, Hao; Liao, Yaling; Zhang, Jin; Wang, Ying; Liu, Zhiyong; Cheng, Ping; Wang, Xingyong; Zou, Quanming; Gu, Jiang (Frontiers in Cellular and Infection Microbiology, 2018)
Escherichia coli (E. coli) K1 causes meningitis and remains an unsolved problem in neonates, despite the application of antibiotics and supportive care. The cross-reactivity of bacterial capsular polysaccharides with human antigens hinders their application as vaccine candidates. Thus, protein antigens could be an alternative strategy for the development of an E. coli K1 vaccine. Outer membrane protein A (OmpA) of E. coli K1 is a potential vaccine candidate because of its predominant contribution to bacterial pathogenesis and sub-cellular localization. However, little progress has been made regarding the use of OmpA for this purpose due to difficulties in OmpA production. In the present study, we first investigated the immunogenicity of the four extracellular loops of OmpA. Using the structure of OmpA, we rationally designed and successfully generated the artificial protein OmpAVac, composed of connected loops from OmpA. Recombinant OmpAVac was successfully produced in E. coli BL21 and behaved as a soluble homogenous monomer in the aqueous phase. Vaccination with OmpAVac induced Th1, Th2 and Th17 immune responses and conferred effective protection in mice. In addition, OmpAVac-specific antibodies were able to mediate opsonophagocytosis and inhibit bacterial invasion, thereby conferring prophylactic protection in E. coli K1-challenged adult mice and neonatal mice. These results suggest that OmpAVac could be a good vaccine candidate for the control of E. coli K1 infection and provide an additional example of structure-based vaccine design.